The Speech Acts in Nali and Salim’s Two Poems (Raparin Journal of Humanities (RJH), 2021)
This study is under the title of “The Speech Acts in Nali and Salim’s Two Poems”. It is an attempt to analyze these two poems in a pragmatic point of view, particularly in terms of speech acts. The significance of speech acts is not to recognize linguistic meaning of words in sentences and utterances, but it is according to the sender’s purpose in the context that they occur. Thus, the language of poetry as a way of using language, especially classical poetry, is not an ordinary language. Consequently, the paper hypothesizes that the speech acts have to be embodied in the poems accurately because there is supposed to be a hidden and invisible meaning in every verse behind its expression and form. The scope of the study is to examine the two poems, and it is benefited from their investigation that has been done in their anthology. In addition, whenever needed, the speech acts are identified in short because much has been mentioned about them in the scientific research institutions.